THE APPLICATION POSSIBILITY OF TAX AS AN INSTRUMENT TO CONTROL THE NEGATIVE IMPACTS OF SWEETENED-BEVERAGE PRODUCTS - Rizky Tiaro Sulistyo; Amrie Firmansyah (IPSAR (International Public Sector Accounting Review), 2023)
Diseases caused by high sugar consumption have become a concern for health problems in various countries. Moreover, in several countries, this disease has become the main cause of the high mortality rate of its population. The high sugar consumption has also led to increased production of sugar-sweetened products. Therefore, efforts are needed to overcome and limit the high consumption and production of non-sugar-friendly products. One of the efforts that the government can implement as a regulator is implementing a tax scheme on sugar-sweetened products. This research aims to review the possibility of implementing taxes to control the negative impacts of beverage products containing sweeteners. This research uses a scoping review method by implementing taxes on products containing sweeteners internationally. The review of this implementation is used as a basis for providing recommendations for its implementation in Indonesia. This research concludes that tax regulations on beverage products containing sweeteners can be used to control people's consumption of sweeteners to maintain their health.